2016
DOI: 10.20286/ijcp-010105
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related Atrioventricular Block: Is It a Benign Condition?

Abstract: Introduction: Prognosis of the patients with beta blocker or calcium channel blocker induced AV block is not well known to date. Methods: All patients with symptomatic second-degree or third-degree atrioventricular block (AV) referred to our institution during one year were recuited prospectively and classified in two groups based on drug consumption (beta blocker/calcium channel blocker versus none). They were followed for six months and then collected data was analyzed. Results:The study included 49 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…In our study, the main cause of reversible high‐degree SND/AVB was bradycardic drugs, mainly beta‐blockers. These results are in agreement with those of previous studies highlighting the incidence of conduction disorders with beta‐blockers 7–9,14,15 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the main cause of reversible high‐degree SND/AVB was bradycardic drugs, mainly beta‐blockers. These results are in agreement with those of previous studies highlighting the incidence of conduction disorders with beta‐blockers 7–9,14,15 …”
Section: Discussionsupporting
confidence: 93%
“…According to current guidelines, permanent pacemaker (PPM) implantation is not indicated in patients with reversible high‐degree AVB or sinus node dysfunction (SND) 6 However, recurrence of high‐degree SND/AVB may occur despite treatment of the cause, leading to PPM at follow‐up 7–9 Indeed, reversible high‐degree SND/AVB may reveal a frailty of the conduction system or automaticity that is likely to reoccur even in the absence of reversible cause 10 …”
Section: Introductionmentioning
confidence: 99%
“…In a study by Zeltser D et al 5 bradycardia persisted in 56% of the patients while it resolved in 41% patients after discontinuation of betablockers and non-DHP CCB. In study done by Sima Sayahet al 19 , AV block persisted in 57% of patients while it resolved in 43% of patients after discontinuation of beta blockers and non-DHP CCBs.…”
Section: Discussionmentioning
confidence: 93%
“…5,18,20 A study by Ovysyshcher IE and Barold SS 4 reported an incidence of 1-15% persistent bradycardia after anti-arrythmic drugs discontinuation, requiring permanent pace maker (PPM) implantation. A study by SimaSayah et al 19 reported recurrence rate for 2 nd and 3 rd degree AV block of 50% after discontinuation of beta and non-DHP CCBs that required permanent pace maker implantation during follow up. A similar study by Osmanov D te al reported recurrence rate of 27% for AV block requiring PPM implantation in nearly half of patients who were on treatment with beta and calcium channel antagonists and digoxin.…”
Section: Discussionmentioning
confidence: 99%
“…5,18,20 A study by Ovysyshcher IE and Barold SS 4 reported an incidence of 1-15% persistent bradycardia after anti-arrythmic drugs discontinuation, requiring permanent pace maker (PPM) implantation. A study by SimaSayah et al 19 reported recurrence rate for 2 nd and 3 rd degree AV block of 50% after discontinuation of beta and non-DHP CCBs that required permanent pace maker implantation during follow up. A similar study by Osmanov D te al reported recurrence rate of 27% for AV block requiring PPM implantation in nearly half of patients who were on treatment with beta and calcium channel antagonists and digoxin.…”
Section: Discussionmentioning
confidence: 99%